Congruency of Separable Affix Verb Combinations Is Linearly Indexed by the N400 - Hanna, Jeff; Pulvermüller, Friedemann (Frontiers in Human Neuroscience, 2018)
Separable affix verbs consist of a stem and a derivational affix, which, in some languages can appear together or in discontinuous, distributed form, e.g. German “aufgreifen” and “greifen … auf” (“up-pick(ing)” and “pick … up”). Certain stems can combine with only certain affixes. However, many such combinations are evaluated not as clearly correct or incorrect, but frequently take an intermediate status with participants rating them ambiguously. Here, we mapped brain responses to combinations of verb stems and affixes realised in short sentences, including more and less common particle verbs, borderline acceptable combinations and clear violations. ERP responses to discontinuous particle verbs were obtained for five affixes re-combined with ten verb stems, situated within short, German sentences i.e. “sie <stem>en es <affix>,” English: “they <stem> it <affix>”. The congruity of combinations was assessed both with behavioural ratings of the stimuli and corpus-derived probability measures. The size of a frontal N400 correlated with the degree of incongruency between stem and affix, as assessed by both measures. Behavioural ratings performed better than corpus-derived measures in predicting N400 magnitudes, and a combined model performed best of all. No evidence for a discrete, right/wrong effect was found. We discuss methodological implications and integrate the results into past research on the N400 and neurophysiological studies on separable-affix verbs, generally.